Human Trafficking Prevalence in Rwanda: The Role Played by Unemployment - John, Gacinya (American Journal of Social Sciences and Humanities, 2019)
Unemployment is the most single factor that facilitates human trafficking in the developing countries such as Rwanda. Rapid population growth constrains wealth creation and so people always migrate to countries of opportunity to escape lack of employment. The aim of this study is to investigate the role of unemployment in determining human trafficking. Quantitative and qualitative approaches were adopted. The target population of the study comprised of 200 respondents and the sample size was 133 respondents. Stratified random sampling technique was used to select the participants from various categories of respondents where as simple random sampling was used in each stratum to get a representative sample. A questionnaire was used to collect primary data. Statistical Package for Social Sciences (SPSS) Version 21 for windows was used as to analyze quantitative data. The findings indicated that R=0.30 and R-Square = 0.09 which is a strong relationship between the independent variables and the dependent variable. The significance of the F-statistic is 0.000 which is less than 0.05. This implies that null hypothesis is rejected and conclude that there is a relationship between unemployment and human trafficking. The proposed model shows that unemployment (Beta = 0.257) was the most important in influencing human trafficking and the Y intercept is 1.476, Thus, the model is written as, Y=1.476+ 0.257X. The study concludes that Human trafficking in Rwanda is prevalent in form of labor and sexual exploitation. To overcome unemployment and therefore human trafficking the government of Rwanda needs to create more jobs.